Risk factors for recurrence in pT3aN0M0 renal cell carcinoma according to 2009 TNM classification - Utsunomiya, Noriaki (Hinyokika kiyo. Acta urologica Japonica, 2014)
The TNM classification of renal cell carcinoma was updated in 2009. In this new classification system, T3a consists of tumors with renal vein involvement and tumors with fat invasion. To assess risk factors for recurrence, we retrospectively reviewed 89 patients with pT3aN0M0 renal cell carcinoma who underwent radical or partial nephrectomy between 1992 and 2011. Analyzed risk factors for recurrence were age, gender, tumor size, grade, v factor, infiltrative growth (INF), adjuvant interferon, surgical technic (radical or partial), clinical T classification, renal vein thrombus, and pathological fat invasion. The median follow-up was 52.2 months. Five-year recurrence-free survival rate was 69.0%. Within the pT3a subcategory, the five-year recurrence-free survival was 76.7% in patients with fat invasion only, 42.9% in patients with renal vein thrombus only, and 28.6% in patients with the two concomitant features. On univariate analysis, tumor size, grade, INF, clinical T classification, and renal vein thrombus were significantly associated with recurrence. On multivariate analysis, INF (p = 0.023, HR 3.927) was an independent risk factor for recurrence. In pT3aN0M0 renal cell carcinoma, INF significantly affects recurrence, and patients with both fat invasion and renal vein thrombus have worst prognosis